The Use of Psychedelics in Chronic Pain – A Scoping Review - Santos, Hugo (2025)
Introduction: Chronic pain (CP) affects a significant portion of the global population. Current therapeutic approaches appear to be insufficient, highlighting the need to explore new options, such as psychedelics. Objectives: To map and compile the literature on the use of psychedelics in CP treatment, detailing study characteristics, included populations, types of psychedelics, and outcomes. Materials and Methods: Studies on the use of psychedelics for CP treatment were analyzed using the Joanna Briggs Institute methodology for scoping reviews. Inclusion criteria: Adults with CP and the use of classic psychedelics. Databases: PubMed, EBSCO, Web of Science, Cochrane, PEDro, and Open Grey Literature Report. Studies in Portuguese, French, English, and Spanish were included. Results: A total of 15 publications were reviewed (clinical trials, observational studies, case studies, and case series studies). It was found that psychedelics, both in macrodoses and microdoses, show therapeutic potential for CP treatment, with studies reporting improvements in pain perception. However, limitations were identified, including methodological variability across studies, lack of specificity in dosing and administration protocols, and the absence of studies combining psychedelics with other recommended therapies. Additionally, some adverse side effects were observed. Conclusion: Psychedelics appear to be promising for CP treatment, but research is still limited and should be approached with caution, considering potential risks. Primary efficacy studies are recommended, and further reviews should be avoided until more primary studies become available.